THE EFFECT OF MINDSET PERSONAL ON BEHAVIOR OF INTERNET ENTREPRENEURSHIP STUDENTS OF UNIVERSITAS PUTRA INDONESIA YPTK PADANG - Muharika Dewi; Erna Susanti; Rina Susanti; Zefri Yenni; Eliza Eliza (Universitas Padjadjaran, 2020)
The importance of understanding mindsets to direct behavior in internet-based entrepreneurship is the effort in bringing entrepreneurial learning processes close to changes in entrepreneurial behavior. This study aims to determine the grouping of students’ mind sets in two growth and fixed categories, knowing the description of mind set content and internet entrepreneurial behavior in students, knowing the differences in internet entrepreneurial behavior based on student mindsets, knowing the correlation between mind set and internet entrepreneurial behavior, then know the contribution of mindset to internet entrepreneurial behavior. This research method with a quantitative approach, using a likert scale questionnaire instrument, the sample is students registered at UPI YPTK Padang in 2018/2019 academic year totaling 148 people, sampling from the population is done by purposive sampling technique, data analysis with percentage techniques in describing data, independent test sample t test for different tests, pearson correlation product moment analysis for testing the relationship of variables and the square of r for testing the contribution. The results of the analysis state that 45% of students with a fixed mind set and 55% with a growth mind set, students with a growth mind set have better internet entrepreneurial behavior with an average of 86.82%. Hypothesis testing states that there are differences in student internet entrepreneurial behavior based on personal mindsets, there is a fairly strong correlation between mind set with internet entrepreneurial behavior, with a contribution of 20.4%. It is proven that students with growth mindsets have higher behavior in internet entrepreneurial activities, therefore to increase the ability and interest of students in entrepreneurship must start from the approach to the correct mindset about entrepreneurship.